Categorization of artwork images based on painters using CNN - Mondal, Kaustav; Anita, H.B (Journal of physics. Conference series, 2021)
Artworks and paintings has been an integral part of human civilization since the dawn of the Stone Age. Paintings gives more insight about any subject compared to the scriptures and documents. Archiving of digital form of paintings helps to preserve the artworks of different painters. The anticipated work is aimed for the classification of painters’ artworks. The artworks of Foreign & Indian painters are considered for the proposed work. The foreign painters’ artworks are obtained from [14]. At present, the Indian painters’ artwork dataset is not readily available. The images were downloaded from the specific genuine website [13]. Conventional Neural Network is used for Feature learning and classification. Around 20k images of artworks is used for the experiment and got an average accuracy of 85.05%.